Utilization of Agricultural Waste from Brebeg Cilacap Village Become Biogas Using Cow Manure - Rosmawati Sipayung; Sonya H. Raharjo; Ebeng Sugondo; Anisa Aprilia (Department of Chemical Engineering, Politeknik Negeri Bandung, 2023)
Straw is one of the most prevalent agricultural wastes in Indonesia, particularly in Cilacap Regency. One hectare of rice fields can yield 7–10 tons of dried straw every growing season. In addition, cow dung in Brebeg Village has not been utilized optimally. Cow dung and straw can be utilized as an alternative energy, one of which is biogas. Biogas is produced through anaerobic fermentation in a biodigester. Methanogenic bacteria first convert straw and cow manure in the biodigester into gas, which is subsequently produced as a high concentration of methane. This technology can be easily applied especially for farmers and ranchers. These experiments were carried out by varying the ratio of cow dung, straw, distilled water, and the percentage of EM-4 bacteria with fermentation for 30 days in each variation. Based on the result, it is known that factors affecting biogas production are ratio of substrate, temperature, pH, and microorganisms. The best biogas is produced with a cow dung, straw, and distilled water ratio of 8:1:2 and 10% EM-4 bacteria with a flash time of 71-seconds and a blue flame. Although a particular sort of plastic is used in this laboratory-scale investigation to make it more efficient, it is prone to leaking. It is advised to use a fixed dome style of storage while scaling up the digester